An improved 2D finite element model for bolt load distribution analysis of composite multi-bolt single-lap joints. (1st December 2020) - Liu, Fengrui; Yao, Wanting; Zhao, Libin; Wu, Hao; Zhang, Xi; Zhang, Jianyu
Abstract: An improved 2D finite element model for bolt load distribution predictions of composite multi-bolt single-lap joints is proposed considering both the efficiency and the accuracy, and this model predicts secondary bending well, which is an important factor for failure of single-lap joints. In this model, the shell element is used to simulate laminates, the fastener technique is used to model bolts, and fasteners are connected to shell elements with coupling constraints. Improvements are mainly reflected in three aspects: (1) replacing the load-displacement curve with the bolt stiffness model to simulate the stiffness of bolts; (2) adding holes on the model of laminates to simulate the stiffness of the joined laminates better; (3) choosing the contact area between bolt head and laminates as the influence region of coupling constraints between the laminates and the bolts to develop the model's ability to simulate the secondary bending. The improvements were validated by comparing the prediction results of the improved model with the results predicted by existing models and 3D finite element models. It is shown that the bolt stiffness model was feasible, the model with bolt holes is more accurate, and annular influence area contributed the good prediction of secondary bending.